2021
DOI: 10.3855/jidc.13922
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmia Risk Profile and Ventricular Repolarization Indices in COVID-19 Patients: A Systematic Review and Meta-Analysis

Abstract: Introduction: Coronavirus disease 2019 (COVID-19) has been associated with cardiac arrhythmias. Several electrocardiographic markers have been used to predict the risk of arrhythmia in patients with COVID-19. We aim to investigate the electrocardiographic (ECG) ventricular repolarization indices in patients with COVID-19. Methodology: We performed a comprehensive systematic literature search from PubMed, EuropePMC, SCOPUS, Cochrane Central Database, and Google Scholar Preprint Servers. The primary endpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Two meta-analyses studied the relationship between COVID-19 and ventricular arrhythmia. However, one of them focused on the patients after chloroquine or hydroxychloroquine treatment (45), while another explored the effect of COVID-19 on QTd, Tp-e/QTc ratio, and Tpe interval (46). In addition, two meta-analyses described the relationship between COVID-19 and all types of arrhythmias (47,48).…”
Section: Compassion With the Previous Studymentioning
confidence: 99%
“…Two meta-analyses studied the relationship between COVID-19 and ventricular arrhythmia. However, one of them focused on the patients after chloroquine or hydroxychloroquine treatment (45), while another explored the effect of COVID-19 on QTd, Tp-e/QTc ratio, and Tpe interval (46). In addition, two meta-analyses described the relationship between COVID-19 and all types of arrhythmias (47,48).…”
Section: Compassion With the Previous Studymentioning
confidence: 99%
“…The literature search provided 810 reviews, 40 of which were eligible for full-text review. After reviewing the full text, 26 meta-analysis studies were eligible for inclusion 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 . The study selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from that, the protein name corresponding to the CaATP_NAI domain of S protein was found from the domain search result file: A0A365XXB7 CaATP_NAI domain-containing protein (Chitinophaga Flava). Besides, the motif sequence corresponding to this protein is “WRHVVHKNMSHRWRM” [ 2 – 31 ], while the S11 of the A0A365XXB7 protein is mutated to A1087 on the S protein. A study shows that due to S/A mutation in N-terminal inhibitory (or the regulatory domain), Ca 2+ -ATPase activity is not inhibited by phosphorylation [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…I NaL prolongs the increase in action potential (AP), leading to arrhythmias and sudden cardiac death [ 30 ]. Here, it should be mentioned that some ECG markers in patients with COVID-19 characterize that SARS-CoV-2 infection is associated with abnormal ion channel function, including Tp-e/QTc, Tp-e interval, and QTd increasing significantly [ 31 ], as well as QRS and QTc [ 32 ], while TDR decreasing, and iCEB value changing dramatically [ 32 ]. The epithelial sodium channel α subunit (ENaC-α) is often found in the same human lung and respiratory cells as ACE2.…”
Section: Introductionmentioning
confidence: 99%